Neuroimaging Correlates of Cerebral Microbleeds: The ARIC Study (Atherosclerosis Risk in Communities). Issue 11 (November 2017) - Graff-Radford, Jonathan; Simino, Jeannette; Kantarci, Kejal; Mosley, Thomas H.; Griswold, Michael E.; Windham, B. Gwen; Sharrett, A. Richey; Albert, Marilyn S.; Gottesman, Rebecca F.; Jack, Clifford R.; Vemuri, Prashanthi; Knopman, David S.
Abstract : Background and Purpose—: Cerebral microbleed (CMB) location (deep versus strictly lobar) may elucidate underlying pathology with deep CMBs being more associated with hypertensive vascular disease and lobar CMBs being more associated with cerebral amyloid angiopathy. The objective of this study was to determine whether neuroimaging signs of vascular disease and Alzheimer pathology are associated with different types of CMBs. Methods—: Among 1677 nondemented ARIC (Atherosclerosis Risk in Communities) participants (mean age=76±5 years; 40% men; 26% black) with 3-Tesla MRI scans at the fifth examination (2011–2013), we fit multinomial logistic regression models to quantify relationships of brain volumes (Alzheimer disease signature regions, total gray matter, frontal gray matter, and white matter hyperintensity volumes), infarct frequencies (lacunar, nonlacunar, and total), and apolipoprotein E (number of ε4 alleles) with CMB location (none, deep/mixed, or strictly lobar CMBs). Models were weighted for the sample selection scheme and adjusted for age, sex, education, hypertension, ever smoking status, diabetes mellitus, race site membership, and estimated intracranial volume (brain volume models only). Results—: Deep/mixed and strictly lobar CMBs had prevalences of 8% and 16%, respectively. Larger white matter hyperintensity burden, greater total infarct frequency, smaller frontal volumes (in women only), and smaller total gray matter volume were associated with greater risk of both deep and lobar CMBs relative to no CMBs. Greater white matter hyperintensity volume was also associated with greater risk of deep relative to lobar CMBs. Higher lacunar and nonlacunar infarct frequencies were associated with higher risk of deep CMBs, whereas smaller Alzheimer disease signature region volume and apolipoprotein E ε4 homozygosity were associated with greater risk of lobar CMBs. Conclusions—: CMBs are a common vascular pathology in the elderly. Markers of hypertensive small-vessel disease may contribute to deep CMBs while cerebral amyloid angiopathy may drive development of lobar CMBs. Abstract : Supplemental Digital Content is available in the text.